Modeling Asymmetric Shift in the Threshold Voltage of MOS Structures under Thermal Field Treatment - O. V. Aleksandrov; N. N. Morozov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Thermal field treatment (TFT) of MOS structures causes instability of the threshold voltage associated with the transport of mobile ions of alkaline earth metal impurities (mainly Na+) in the electric field of the gate dielectric. Experimental kinetics of accumulation and restoration of the mobile charge during TFT deviate from the known descriptions by Snow’s diffusion and Hofstein’s boundary capture models.Aim. Development of a quantitative model for the behavior of MOS structures during thermal field treatment in the modes of accumulation and restoration of the mobile charge of an ionic impurity.Materials and methods. The model is based on the analysis of the capture kinetics of mobile impurity ions on polyenergetic traps in the volume of an amorphous gate dielectric. Following the analysis of physical processes, a system of differential equations is compiled and solved by the finite difference method using explicit and implicit difference schemes.Results. The conducted comparison of the data calculated by the developed model and the experimental data reported in literature for the time dependencies of the threshold voltage shift of MOS structures with positive and subsequent negative gate bias determined the range of binding energies, the characteristic dispersion energy, the concentrations of impurity ions and traps near the gate and the silicon substrate, and the width of the region of their localization. A decrease in the range of binding energies in the vicinity of the SiO2–Si interface compared to the SiO2–metal gate interface was found, which may indicate the presence of an ordered thin SiO2 layer in the vicinity of silicon.Conclusion. It was shown that the charge recovery process occurs at a higher rate than the accumulation process due to the difference in the distribution of traps in the vicinity of the interphase boundaries of SiO2 with the silicon substrate and with the gate. The proposed model can be used to describe the experimental asymmetric behavior of MOS structures contaminated with alkaline earth metal ions during TFT.